Pengaruh Harga, Motivasi Hedonis dan Persepsi Kemudahan Terhadap Keputusan Pembelian Virtual Item Pada Game Online Mobile Legends - Ida Bagus Raka Suardana; Winda Aliya Agustin (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of the online gaming industry in Indonesia shows a rapidly growing trend, one of which is reflected in the high level of virtual item purchases in Mobile Legends. This phenomenon is important to examine because digital consumer behavior exhibits patterns that differ from conventional consumption behavior. This study aims to analyze the influence of price, hedonic motivation, and perceived ease of use on the decision to purchase virtual items in the Mobile Legends game. The theoretical foundation employed is consumer behavior theory. This research uses a quantitative method with an explanatory approach. The sample was drawn from the population of Mobile Legends players in Denpasar City using a random sampling technique, resulting in 140 respondents. Data were collected through an online questionnaire using a five-point Likert scale, and analyzed using multiple linear regression. The findings indicate that price, hedonic motivation, and perceived ease of use have both partial and simultaneous effects on virtual item purchase decisions in Mobile Legends. The contribution of these variables to purchase decisions is 58.6%. Developers of Mobile Legends are advised to adjust pricing based on value perception and player feedback, enhance aesthetic and personalization elements to strengthen hedonic motivation, and simplify payment processes through digital wallet integration and instant purchase options to ensure a more effortless transaction experience.